Philological Analysis on Normative Historical Practical Term Rahmah in Qur’an - Rosidin Rosidin; Handoko Ja’far (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The article philologically analyzes the term rahmah through four data sources. First, al-Qur’an that often mentioned the term rahmah 563 times in 422 verses. Second, the book Shahih Bukhari-Muslim that sets forth the socialization of the term rahmah from insider perspective on the teachings and normative examples of Muhammad. Third, the book Muhammad: His Life Based on the Earliest Sourcesby Martin Lings andThe Venture of Islam byMarshall Hodgson that summonses rahmah socialization from outsider perspective through the life of prophet and muslim.Fourth, the book Ihya’ ‘Ulum al-Dinby al-Ghazali and Toward a Global Civilization of Love and Toleranceby Fethullah Gulen that describes rahmah practice as a way of life for classic and contemporary sufi. By means of three stages philological analysis: Information-socialization-transformation, there are three claims of this article. Information phase, normative definition of term rahmah is a universal affection addressed to all creatures in universe. Socialization phase, normative definition of term rahmah socialized thru the teaching and normative examples of prophet, who assigns rahmah as an identity of muslim whether they are in minority status nor majority one. Rahmah practice socialization strengthened by the life of prophet and Muslim with affection domination rather than hatred. In transformation phase, rahmah appeared asa classic and contemporary sufistic life style that actively spread affection to all creatures with no insight of girded exoteric status. يحلل المقال فلسفيًا مصطلح رحمة من خلال أربعة مصادر للبيانات. أولاً ، القرآن الذي غالبًا ما يذكر مصطلح